(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2020)
Buffaloes is performance and potensial has ideal as meat-producing livestock, but the population has declined each year. The purpose of this research was to analyze performance and development strategy of swamp buffalo in Serang District. The resarch metodology was using the Body Condition Score (BCS) system and the analysis of Strength, Weakness, Opportunity, Threat (SWOT). The research was conducted in Serang District with a survey method, observation and in-depth interviews to 50 farmers, with the snowball sampling, and reinforced with secondary data from the instance relevant. The research location was determined by purposive sampling. Data obtained from 36 buffaloes randomly with the range of age before and after sexual maturity with a different sex, through direct observation using a frame-size Body Condition Scores (BCS). Analysis BCS calculations using factorial completely randomized design. The analysis showed that bulls have better of Body Condition Scores (BCS) level than cows when subjected to sexual maturity. The result value of the interaction between age and sex was significant (P<0.05), so there were SWOT that differs between the interactions with one another. The SWOT analysis and Quantitative Strategic Planning (QSP): the priority was to improve the weaknesses of alternative strategies to avoid threats, the strategy was to strengthen the organizational/institutional breeders that have a strong bargaining power in order to increase the population of buffaloes and breeder ability.